Combining multiple technologies: integrated soil fertility management - Bekunda, Mateete A.; Chikowo, Regis; Claessens, Lieven; Hoeschle-Zeledon, Irmgard; Kihara, Job Maguta; Kizito, Fred; Okori, Patrick; Sognigbé, N'Danikou; Thierfelder, Christian L. (CAB International, 2022)
This chapter shows how Integrated Soil Fertility Management (ISFM) can be combined and integrated further at farm and landscape levels to improve farming system performance. ISFM is an example of a system-wide technology. It is a set of soil fertility management practices, including use of industrial fertilizer, organic inputs, and improved crop varieties, combined with knowledge on how to adapt the practices to local conditions. Its benefits include agronomic efficiency, enhanced productivity, reduced risk, reduced need for industrial fertilizers, and reduction in post-harvest losses. The farmers' responses and opportunities for adoption are also discussed.